2018
DOI: 10.1002/alr.22274
|View full text |Cite
|
Sign up to set email alerts
|

Semaphorin 3A inhibits allergic inflammation by regulating immune responses in a mouse model of allergic rhinitis

Abstract: Background: It has been reported that semaphorin 3A (sema3A) could improve allergic symptoms in allergic rhinitis (AR) mice. However, the immunomodulatory roles of sema3A in AR remain unclear. This study was performed to determine the immunoregulatory effects of sema3A on airway inflammation in an AR mice model. Methods:First, sema3A expression was measured in the serum of AR patients and also in a mice model. Then, nasal symptoms, ovalbumin (OVA)-specific immunoglobulin E (IgE) production, cytokine levels, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…CD4 + IL-17 + Th17 cells were once discovered to induce autoimmune disorders [ 49 ]. Xiang et al’s study showed that sema3A which can exert immunoregulatory effect pulled down the raised percentage of CD4 + IL-17 + Th17 cells and inhibited allergic inflammation in OVA-induced mice [ 50 ]. Likewise, we found a high ratio of CD4 + IL-17 + Th17 cells to CD4 + T cells in RA mice, while CGA application lowered this ratio.…”
Section: Discussionmentioning
confidence: 99%
“…CD4 + IL-17 + Th17 cells were once discovered to induce autoimmune disorders [ 49 ]. Xiang et al’s study showed that sema3A which can exert immunoregulatory effect pulled down the raised percentage of CD4 + IL-17 + Th17 cells and inhibited allergic inflammation in OVA-induced mice [ 50 ]. Likewise, we found a high ratio of CD4 + IL-17 + Th17 cells to CD4 + T cells in RA mice, while CGA application lowered this ratio.…”
Section: Discussionmentioning
confidence: 99%
“…We assume that this effect is achieved by increasing local Treg functions, which subsequently reduces adaptive immune-mediated responses and pro-inflammatory cytokines. It is also possible that sema3A inhibits IL-17 production, indirectly leading to the reduced influx of neutrophils, although experimental proof for that is still required (29). So far there is no evidence for the presence of sema3A receptors on neutrophils and eosinophils.…”
Section: Discussionmentioning
confidence: 99%
“…The AR murine model was established as previously described ( 17 ) with minor modifications (the mice were intranasally challenged on days 21–28). The miR-31 agomir was purchased from Guangzhou RiboBio Co., Ltd.…”
Section: Methodsmentioning
confidence: 99%